2008
DOI: 10.1002/bjs.6071
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of materials eliciting foreign body reaction in stapled human gastrointestinal anastomoses

Abstract: The presence of foreign body reaction was confirmed in stapled human gastrointestinal anastomoses. The source of refractile materials eliciting this reaction was the stapler cartridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…13 In a porcine model, minimal fibrosis around the titanium staples was reported with only an occasional foreign-body giant-cell reaction. 14 However, Klein et al, 15 in the study in which a rat model was used, reported that there were no significant differences in fibrous tissue formation between titanium and absorbable polymeric surgical clips at any time.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a porcine model, minimal fibrosis around the titanium staples was reported with only an occasional foreign-body giant-cell reaction. 14 However, Klein et al, 15 in the study in which a rat model was used, reported that there were no significant differences in fibrous tissue formation between titanium and absorbable polymeric surgical clips at any time.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Similar changes can also be seen in patients with metal allergies, such as nickel and/or titanium, who have abdominal surgery requiring use of stapling devices. 17,18 This actively inflamed gastric ulcer contains fibrin-rich granulation tissue with mixed inflammation, including numerous eosinophils (c). Sheets of eosinophils persist in the muscularis mucosae of a healing ulcer (d).…”
Section: Eosinophils As a Component Of Mixed Inflammationmentioning
confidence: 99%
“…11 Lim et al confirmed the presence of foreign body reaction in stapled human GI anastomoses, the source of foreign materials eliciting this reaction being stapler cartridges. 12 Among the American and European surgeons who were trained in surgery at the end of the twentieth century, staplers were called “Russian Gun”. 13 …”
Section: Discussionmentioning
confidence: 99%